Distribution functions and statistical parameters that may be used to characterize limb sounders gravity wave climatologies in the stratosphere - Alexander, Pedro Manfredo (2015)
The number of gravity wave (GW) activity climatologies in the stratosphere started to increase more than 10 years ago since the appearance of large amounts of limb and nadir satellite sounders data. There have been very few discussions regarding the adequate statistical description of GW activity in terms of a distribution function and its parameters. We put forward the question whether a general statistical functional representation adaptable to the characteristics of GW activity in diverse geographic regions and seasons exists. Here we approach this issue for two different types of limb sounders and in particular we try to find out which parameters may represent at best the climatological features. We study results for a region close to the Patagonian Andes and their prolongation in the Antarctic Peninsula, which is well-known for the generation by topography of intense stratospheric GW, specially during winter and spring. Global Positioning System (GPS) radio occultation (RO) records presently provide over 2000 profiles per day. We used 5 years of COSMIC (Constellation Observing System for Meteorology, Ionosphere and Climate) mission GPS RO data, which supplied almost 150,000 retrievals for our study. Three different distribution functions have been approached to describe the GW activity climatologies: gaussian, log-normal and gamma. The latter function has not been used in previous work. It has been shown here that it is a competitive option to the log-normal distribution. In addition, its use allows not only to quantify the GW activity level of each climatology in the stratosphere, but also to find out the number of significant modes that essentially determine it. Alternative parameters to the mean like the median may be used to characterize the climatologies. The use of the median may exhibit advantages in cases where the presence of spurious large GW activity measurements are suspected in GPS RO data. The mean is equally suitable to establish GW activity comparisons. As a priori we may not know if the above mentioned artifacts are present, in general it may be more appropriate to use the median. We perform a similar general study for data from the SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) limb instrument, as it is presently also used to obtain global GW climatologies in the stratosphere. Although the observational window and data processing features are not identical for both instruments, the results exhibit many similarities.